A micro channel‐cut crystal X‐ray monochromator for a self‐seeded hard X‐ray free‐electron laser. (27th August 2019) - Osaka, Taito; Inoue, Ichiro; Kinjo, Ryota; Hirano, Takashi; Morioka, Yuki; Sano, Yasuhisa; Yamauchi, Kazuto; Yabashi, Makina
Abstract : A channel‐cut Si(111) crystal X‐ray monochromator with a channel width of 90 µm was developed for achieving reflection self‐seeding in hard X‐ray free‐electron lasers. A high conversion efficiency of a monochromatic seed from a broadband X‐ray beam was experimentally evaluated to be 2 × 10 –2 with a small optical delay of 119 fs at 10 keV. Abstract : A channel‐cut Si(111) crystal with a channel width of 90 µm was developed for achieving reflection self‐seeding in hard X‐ray free‐electron lasers (XFELs). With the crystal a monochromatic seed pulse is produced from a broadband XFEL pulse generated in the first undulator section with an optical delay of 119 fs at 10 keV. The small optical delay allows a temporal overlap between the seed optical pulse and the electron bunch by using a small magnetic chicane for the electron beam placed between two undulator sections. Peak reflectivity reached 67%, which is reasonable compared with the theoretical value of 81%. By using this monochromator, a monochromatic seed pulse without broadband background in the spectrum was obtained at SACLA with a conversion efficiency from a broadband XFEL pulse of 2 × 10 −2, which is ∼10 times higher than the theoretical efficiency of transmission self‐seeding using a thin diamond (400) monochromator.